Venetian Diplomacy and the Great Horde in the 1470’s. - V.P. Gulevich (Золотоордынское обозрение)
Objective: To investigate Republic of San Marco’s attempts to engage the Great Horde Tatars in war against the Ottoman Empire and find out their consequences. Research materials: The research based on archive documents published in Venice, the Annals of Jan Długosz, the chronicles of the Northeast Russia, as well as Turkish-Horde diplomatic correspondence materials. Results and scientific novelty: After the fall of Constantinople in 1453, the trading posts of Venice, in the Black and Azov seas were under the greatest threat. They had not enough forces in Venice for the war with the Ottomans. The Venetian Senate was constantly searching for allies to create an anti-Ottoman coalition. In addition to European countries, Venice saw the Ak-Koyunlu and the Great Horde among them. Drawing the Polish Kingdom into the war failed, and the Ak-Koynulu was defeated by the Turks. In this connection, the Venetian Senate paid particular attention to the Great Horde. But many objective factors prevented the successful implementation of Venetian plans, such as: the distance from the Great Horde to Venice and the Balkans, the reluctance of the Polish king Casimir IV giving a way to the Great Horde Tatars through his land, suspicion of the Moscow ruler Ivan III, and the Venetians erroneous assessment of Ahmad Khan’s desires and possibilities. The situation was complicated for the Venetians by the rapidly changing setting in the northern Black Sea region due to the Ottoman wars in the mid–1470’s against the Moldavian principality, their seizure of southern coast of the Crimea and the subordination of the Crimean Khanate. Ahmad Khan’s ambassadors’ arrival in Venice was unable to accelerate the implementation of the Venetian Senate plans. Furthermore, in the 1470’s, Ottoman diplomacy did not leave without attention the northern Black Sea region and after a long break regained embassies exchange with the Great Horde. Venetian diplomats’ reinforced efforts were unable to overcome the resistance of Casimir IV, and Venice was forced to abandon its plans.